Analysis Employee Expenditure, Goods and Services Expenditure, Capital Expenditure on the Financial Performance of Regional Apparatus Organisations in Supporting Sustainable Development of the Bangkalan Regency Government - Dimas Cakraningrat; Agus Sukoco (IJEBD (International Journal of Entrepreneurship and Business Development))
Purpose: This study was conducted to test and analyse the effect of Personnel Expenditure, Goods and Services Expenditure, Capital Expenditure on the Financial Performance of Regional Apparatus Organisations in Supporting Sustainable Development of the Bangkalan Regency Government.